Starvation-Induced Thermal Tolerance as a Survival Mechanism in a Psychrophilic Marine Bacterium - Preyer, Janet M. (1993)
Carbon-starved cultures of strain Ant-300, a psychrophilic marine vibrio isolated from the Antarctic Convergence, were compared with their nonstarved counterparts for resistance to heat. Specifically, starved and unstarved cells were exposed to 17°C, which is 4°C above the maximum growth temperature, and compared with cells maintained at the optimum temperature (5 to 7°C). Total cell counts, direct viable-cell counts, and plate counts were monitored. At a temperature of 17°C, viability (as indicated by plate counts) was lost within 40 h, with direct viable-cell counts indicating less than 5% viability at this time. However, when cells were carbon starved for 1 week prior to heat challenge, significant plateability was maintained for more than 6 days; direct viable-cell counts of starved cells maintained at 17°C indicated the presence of viable cells for at least 12 days. Because starvation is the normal physiological state of copiotrophic, heterotrophic bacteria in oligotrophic marine waters, these data suggest that starvation conditions may be a significant factor in providing heat tolerance to psychrophiles.